THE MANAGEMENT OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN THE INTEGRATED PRIVATE ISLAMIC ELEMENTARY SCHOOL OF HIKMATUL FADHILLAH MEDAN - Elpi Sukaesi Ritonga, Candra Wijaya, Ali Imran Sinaga (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2019)
Abstract: This study aims to (1) Describe the management of Islamic religious educationlearning in the Integrated Private Islamic Elementary School of Hikmatul Fadhillah Medan (2)Knowing the obstacles and solutions in the management of Islamic religious education learningin the Integrated Private Islamic Elementary School of Hikmatul Fadhillah Medan. The researchmethod used is a qualitative research method using data collection techniques in the form ofobservation, interviews, and documentation studies by emphasizing information data sourcesnamely: principals and Islamic religion teachers, to confirm the validity of the data obtained.The validity of the data uses triangulation of data and sources. Data analysis using an interactivemodel consists of data collection, data presentation, data reduction and conclusion drawing.The results showed that: (1) Management of teacher learning Islamic Religious Education inHikmatul Fadhillah Integrated Islamic Private Elementary School in Medan is done throughplanning, organizing, learning and evaluating learning with an assessment system, (2) Obstaclesin the management of teacher learning Islamic Religious Education in Hikmatul Fadhillah IntegratedIslamic Private Elementary School Medan is less than optimal in applying existing learningmethods. In addition, teachers are also less able to be creative in the learning methods appliedand optimize them. While the inhibiting factors of students’ lack of interest in student learning,and some students are not fluent in reading and writing the Koran. The solution in the managementof Islamic education teacher learning in the Integrated Islamic Private Elementary School ofHikmatul Fadhillah Medan is that the teacher always motivates and also calls the tahsin andtahfidz teachers from outside to help students who are not fluent in reading and writing theKoran letters. The solution for teachers is that schools improve the quality of teacher professionalismthrough educational seminars providing training in learning methodologies, training in makingsimple teaching aids, computer training and others.Keywords: Management, Learning, Islamic Religious Education